Integrity of nursing students in Israel: An exploratory study. (October 2022) - Kay, Avi; Polin, Brian A.; Sadeh, Shira
Abstract: Aim: Research regarding the relationship between academic year and age and academic integrity is ambiguous; and at times confounded by a conflation of the terms "age" and "academic year." This research aims to disentangle age from academic year and to assess the possible impact of those two factors on academic integrity. Background: There is a growing concern regarding the lack of academic integrity among nursing students. The lack of academic integrity not only undermines the ability of academic institutions to accurately assess the professional training of nursing students, but also poses a danger to those who may ultimately depend on these nurses for treatment. Design: Cross-sectional analysis of self-report measures of nursing students. Methods: In the Fall of 2020, 143 nursing students at a faith-based academic institution in Israel completed an online, anonymous questionnaire addressing academic integrity and background demographics of respondents (i.e. age, academic year, sex). Results: No general trends regarding dishonesty and academic year or age emerged, though advanced students reported being less honest on work-based presentations. Also, differences emerged in self-acknowledged frequency of the different forms of cheating. Cheating on exams is the least frequent of all the forms of cheating, while enabling others to cheat was the most frequent type. Conclusions: We hypothesized that academic dishonesty would decrease with both age and academic year. No such overall trend emerged when all cheating items are considered as an unweighted 'cheating index.' However, there were differences among different types of cheating. Cheating on exams is the least frequent of all the forms of cheating, while enabling others to cheat is engaged in most frequently and presumably perceived to be the most benign. Enabling others may be related to the communal nature of Israeli society and further amplified by the homogenous nature of the student body. Also, it is suggested that differences between cheating on familiar methods of evaluation (e.g. tests) and unfamiliar methods, which the students only experience as they advance in their degree (e.g. case studies) is a function of their gradual exposure to these novel methods. It is suggested that further research regarding this matter is warranted. Finally, the possible importance of the findings for those interested in advancing academic integrity are discussed, with a focus on how cultural matters and the novelty of forms of evaluation should be addressed to advance academic integrity among student as they advance in their studies.